2021
DOI: 10.3390/brainsci12010058
|View full text |Cite
|
Sign up to set email alerts
|

Blinding in tDCS Studies: Correct End-of-Study Guess Does Not Moderate the Effects on Associative and Working Memory

Abstract: Transcranial direct current stimulation (tDCS) has become a valuable tool in cognitive neuroscience research as it enables causal inferences about neural underpinnings of cognition. However, studies using tDCS to modulate cognitive functions often yield inconsistent findings. Hence, there is an increasing interest in factors that may moderate the effects, one of which is the participants’ beliefs of the tDCS condition (i.e., real or sham) they received. Namely, whether participants’ correct guessing of sham co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Therefore, we decided to set in other mechanisms to minimize potential experimenter effects, such as protocol-blind data management. In addition, we argue that using the automatic assessment tools and scoring additionally decreases the potential bias [83,97].…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, we decided to set in other mechanisms to minimize potential experimenter effects, such as protocol-blind data management. In addition, we argue that using the automatic assessment tools and scoring additionally decreases the potential bias [83,97].…”
Section: Discussionmentioning
confidence: 96%
“…Participants in the active tDCS group had significantly lower ratings than those in the sham tDCS group, which could have resulted from the greater scalp sensations in the active tDCS group. In general, this pattern of results could suggest that the active tDCS groups were not fully blinded to their tDCS condition assignment, and this could have impacted their cognitive–motor multitasking performance, akin to a placebo effect [ 93 , 94 , 95 ], although correctly guessing stimulation condition does not necessarily alter the effects of tDCS on performance [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…The blinding procedure using the well-established fade-in/out sham protocol in this study has proven to be an effective way of keeping participants unaware of the stimulation conditions they receive [ 32 , 33 ]. However, it has been argued that experiments with a repeated-measures design can be more sensitive to unblinding since participants undergo multiple sessions, which they can compare with respect to sensations they felt during stimulation and with respect to their subjective level of performance [ 34 ]. It has been shown that the fade-in/out sham protocol mimics real stimulation successfully and cannot be guessed by participants [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been argued that experiments with a repeated-measures design can be more sensitive to unblinding since participants undergo multiple sessions, which they can compare with respect to sensations they felt during stimulation and with respect to their subjective level of performance [ 34 ]. It has been shown that the fade-in/out sham protocol mimics real stimulation successfully and cannot be guessed by participants [ 34 ]. In addition, the control condition without a target leaves no way to accurately assess the performance in the distractor-induced deafness, so it can be assumed that the procedure chosen here was unproblematic with respect to sham guessing.…”
Section: Discussionmentioning
confidence: 99%